The Idea of Pakistan: From Lahore Resolution to Partition through Literature (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Lahore Resolution first put the idea of Pakistan officially in the forefront of Indian Politics seekingindependent and sovereign units. Right after Lahore Resolution was passed it was debatedvehemently in literary circles. Many books, Pamphlets and articles were published discussing anddebating the idea and feasibility of Pakistan. This Paper tries to explore the idea of Pakistan throughliterature right from its inception in Lahore Resolution to Partition.